Application of the Forward Chaining Method to Evaluate Lecturer Performance in Learning at the Kuantan Singingi Islamic University - Helpi Nopriandi; Nofri Wandi Al-Hafiz (Institute of Computer Science (IOCS), 2020)
Kuantan Singingi Islamic University Is a combination of three high schools in Kuantan Singingi Regency, Riau Province, has 4 Faculties with 13 Study Programs and 97 permanent lecturers and 3 non-permanent lecturers, whose main tasks are: transforming, developing, and disseminating science, technology. , and arts through education, research, and community service. Application of the Forward Chaining Method in which the inferencing engine uses user-defined information to move to AND and OR logic until an object is determined. All rules must be met so that one object will be achieved. This method is used for the process of evaluating the performance of lecturers in learning at the Kuantan Singingi Islamic University. This system will later be created using the web-based programming languages PHP and MySQL and converted into android which will be used by students in assessing lecturers who have carried out learning each semester. This system also makes it easier for LPMP to make decisions about the learning process that has been carried out by the lecturers.